Depression, anxiety, and stress levels in Denpasar community during the pandemic of Corona Virus Disease 2019 (COVID-19) - I Gusti Ngurah Bagus Rai Mulya Hartawan; I Gede Gita Sastrawan; Rovie Hikari Parastan; Luh Seri Ani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
The Government of Indonesia has started to implement a Large-Scale Social Limitation (PSBB) in cities and provinces in Indonesia to prevent the increasing of COVID-19 transmission. The Denpasar city as one of the cities that implemented a similar system. This study was aims to provide an overview of the levels of depression, anxiety, and stress in the Denpasar community during the COVID-19 pandemic. This study was an observational descriptive study with cross-sectional design. The data collection used Google forms that distributed online. There were 160 respondents participated in this study, dominated by women (56.9%), domiciled in South Denpasar (35.0%), living with family or relatives (85.6%), aged 18-25 years old (63.7%), had diploma or bachelor degree as their education background (55.0%), unmarried (66.3%), students (38.8%), and no income (44.4%). The results showed that respondents had 1-2 offspring (53.7%), did not experience layoffs (83.9%), and experienced a decrease in income (67.0%), dominant respondents experienced psychosocial disorders in the form of depression (51.2%) with a moderate degree (31.7%) and the anxiety (53.1%) with a mild degree (40.0%). Most respondents did not experience stress (53.1%). In conclusion, the characteristics of respondents' psychosocial disorders were moderate depression, mild anxiety, and did not stress.